Comprehensive evaluation of siRNA therapeutics on Lp(a): a network meta-analysis - Liu, Song; Wang, Xingjin; Hu, Jiaqiang; Zhao, Chen; Qin, Xiaoli (Diabetes, obesity and metabolism, 2025)
AIMS: To evaluate the efficacy and safety of siRNA drugs that lower Lp(a) in patients with dyslipidaemia. - MATERIALS AND METHODS: A network meta-analysis and systematic review were conducted to compare siRNA drugs targeting Lp(a), based on relevant randomized controlled trials (RCTs). A comprehensive search was performed in PubMed, Embase, Web of Science and the Cochrane Library (up to October 24, 2024). RCTs with an intervention duration of at least 12 weeks were included. Eligible studies compared siRNA drugs that reduce Lp(a), including both Lp(a)-targeted and non-targeted agents, with placebo or other siRNA drugs that reduce Lp(a). The primary outcomes were the percentage reduction and absolute reduction in Lp(a), percentage reduction in low-density lipoprotein cholesterol (LDL-C), percentage reduction in apolipoprotein B (apo(B)), adverse events and serious adverse events, including injection-site reactions. The risk of bias was assessed using the Cochrane Risk of Bias Tool (ROB2), and a random-effects network meta-analysis was performed using the frequentist approach. Confidence in effect estimates was evaluated using the Confidence In Network Meta-Analysis (CINeMA) framework. - RESULTS: A total of 14 trials involving 5646 participants were included. Lp(a)-targeted siRNA agents, particularly Olpasiran, demonstrated strong efficacy in significantly reducing Lp(a) levels, with the greatest percentage reduction in Lp(a) (mean difference [MD]: -92.06%; 95% CI: -102.43% to -81.69%; P-score: 0.98). Olpasiran also showed the greatest absolute reduction in Lp(a) (MD: -250.70 nmol/L; 95% confidence interval [CI]: -279.89 to -221.50; P-score: 0.99). Certain non-Lp(a)-targeted siRNA agents, such as inclisiran and zodasiran, also showed modest reductions in Lp(a) levels, reducing Lp(a) by approximately 15%. Lp(a)-targeted siRNA agents reduced LDL-C by more than 20% and decreased apo(B) by approximately 15%. In terms of safety, most drugs exhibited favourable safety profiles with no significant differences compared to placebo. However, zerlasiran raised concerns regarding injection-site reactions and other adverse events when compared to placebo. - CONCLUSIONS: Lp(a)-targeted siRNA agents have shown robust effectiveness in substantially reducing Lp(a) levels, including both percentage and absolute reductions, with moderate improvements in LDL-C and apo(B) concentrations. Non-Lp(a)-targeted siRNA agents also demonstrate modest reductions in Lp(a) levels. The safety profile is generally favourable, but zerlasiran and inclisiran may increase the incidence of injection-site reactions.
Gesehen am 16.12.2025